The design and implementation of a configurable MIMO detection system on the NOC-based multicore platform. (October 2016) - Hsu, Po-Jen; Tseng, Yu-Hao; Chen, Wei-Jhe; Shen, Chung-An
Abstract: This paper presents the design and implementation of a configurable and scalable MIMO detection system based on the multicore platform where the computation nodes are interconnected using the Network-on-Chip (NOC) paradigm. In this system, a tree-searching based MIMO detection algorithm is revised to be suitable for the NOC system, and the processing elements that execute the algorithm is architected. The mapping methodology of the algorithm onto the NOC platform is presented and the structure and operation of the entire MIMO detection scheme is illustrated. Furthermore, two types of NOC topologies are implemented in order to elucidate the design trade-offs between the processing speed and the system complexity. We show that the proposed MIMO detection scheme is highly configurable to support different system configurations including number of antennas and modulation schemes, and is suitable for large-scale MIMO system that equips with large number of antennas. The proposed NOC-based MIMO detection scheme has been implemented on the Field Programmable Logic Array (FPGA). The analyses of time complexity and experimental results based on the FPGA are both presented in this paper.